Peran Masyarakat Adat Kalaodi dalam Penanggulangan Covid-19 di Kelurahan Kalaodi - Ikmal Muhammad; Ismail Maulud (Universitas Khairun, 2020)
Tidore is one of the town that called a thousand of Jin’s town. This is related to the story from the faunding father from thousand years ago. In doing every thing that need more power of human being, they usually used the Jin’s power to help them in daily life. Not only that, they usully used the Jin to protect them from dangerous as like to help them in war for freedom of indonesia, and so on. Kalaodi society still do what their faunding fathers do in the past to solve the problem. They also do this ritual to save their family or the comunity when there has a problem comes around them, as like a conflict hapended in 1999. Tidore’s comunity aspecialy kalaodi comunity, based on all experiences in the past, they used the power of jin to help them to save their comunity although it is imposible to believe in human main. In 2020 the corona virus or covid-19 hapend in indonesia until now, the goverment always make an intstuction how to solve the problem by using 3M. Kalaodi society belive that corona virus is coming from supra natural desease so, if to over come this virus it should use the power of supra natural too.Key words; the roll of society, social custom, cultural value.